L-Lysine-Linked Modular Fluorescent Cholesteryl Mimics: Biophysical Properties, Molecular Interactions, and Cellular Applications - Nicholas McInchak; Laura Stawikowska; Haylee Mesa; Jonathan Meade; Qi Zhang; Maciej J. Stawikowski (Sci)
Fluorescent cholesterol probes are indispensable tools for studying membrane structure, dynamics, and trafficking. To better understand the structure–function relationship of fluorescent cholesteryl probes, we developed a series of five new modular naphthalimide-containing cholesteryl probes (CND15–CND19). These probes incorporate an L-lysine linker between the cholesterol moiety and the fluorophore, along with a series of distinct head groups. We conducted extensive biophysical characterizations of these probes, including the determination of their solvatochromic properties and lipid partitioning behavior using giant unilamellar vesicles. Molecular dynamics simulations were employed to identify key molecular interactions of these probes within model lipid membranes. Furthermore, live-cell imaging in 3T3 fibroblasts demonstrated the potential applications of these analogs in live-cell imaging, measuring cellular membrane dynamics and studying cholesterol-related processes. The results of this study underscore the critical role of the linker and head group in designing fluorescent cholesterol-mimicking probes. These findings provide valuable insights into optimizing probe designs for future cholesterol and membrane biology research.